Clinically, what ought we to believe?. (February 2019) - Little, John D; Davison, Lorraine; Little, Robert D
Objective: To question the status of the randomised controlled trial (RCT) in the hierarchy of evidence. Conclusions: The RCT provides important and clinically relevant information, particularly in psychopharmacology. However, and as with other methodologies, RCTs too are flawed and automatic abdication to their conclusions, especially in complex social interventions, is unwise. A clinical example with conflicting and polarising views, each with their evidence base, is described alongside a suggested clinical strategy for resolving differences of opinion.